Human milk pasteurisation reduces pre-lipolysis but not digestive lipolysis and moderately decreases intestinal lipid uptake in a combination of preterm infant in vitro models. (1st November 2020) - Vincent, Marine; Ménard, Olivia; Etienne, Julie; Ossemond, Jordane; Durand, Annie; Buffin, Rachel; Loizon, Emmanuelle; Meugnier, Emmanuelle; Deglaire, Amélie; Dupont, Didier; Picaud, Jean-Charles; Knibbe, Carole; et al.
Highlights: An updated in vitro digestive lipolysis model was adapted to preterm infant conditions. Lower prelipolysis but similar digestive lipolysis were obtained in pasteurised vs raw human milk. Intracellular lipid droplets were quantified by an adapted image analysis method. Mean lipid droplet area in Caco-2 cells was smaller with pasteurised than with raw human milk. Abstract: Donor human milk, pasteurised for safety reasons, is the first alternative for feeding preterm infants when mothers' own milk is unavailable. Breastmilk pasteurisation impact on lipid digestion and absorption was evaluated by a static in vitro digestion model for preterm infants coupled with intestinal absorption using Caco-2/TC7 cells. Lipid absorption was quantified by digital image analysis of lipid droplets, by measurement of basolateral triglyceride concentration and by analysing the expression of major genes involved. After in vitro digestion, lipolysis extent was 13% lower in pasteurised human milk (PHM) than in raw human milk (RHM). In Caco-2/TC7 cells, the number of lipid droplets was identical for both milk types, while the mean droplet area was 17% smaller with PHM. Altogether, pasteurisation decreased the pre-lipolysis of human milk. This initial difference in free fatty acid amount was only partially buffered by the subsequent processes of in vitro digestion and cellular lipid absorption.